Engineered three-dimensional bioactive scaffold for enhanced bone regeneration through modulating transplanted adipose derived mesenchymal stem cell and stimulating angiogenesis - Wang, Gan; Cui, Yutao; Leng, Yi; Sun, Shouye; Yuan, Baoming; Liu, He; Peng, Chuangang; Wu, Dankai (Frontiers in Bioengineering and Biotechnology, 2024)
Titanium alloy materials are commonly used in orthopedic clinical treatments. However, conventional titanium implants usually lead to insufficient bone regeneration and integration because of mismatched biomechanics and poor bioactivities. To tackle these challenges, a porous titanium alloy scaffold with suitable mechanical properties was prepared using three-dimensional (3D) printing, and then an adipose-derived mesenchymal stem cell (ADSC) loaded platelet-rich plasma (PRP) gel was placed into the pores of the porous scaffold to construct a bioactive scaffold with dual functions of enhancing angiogenesis and osteogenesis. This bioactive scaffold showed good biocompatibility and supported cell viability proliferation and morphology of encapsulated ADSCs. Osteogenic and angiogenic growth factors in the PRP gel promoted the migration and angiogenesis of human umbilical vein endothelial cells (HUVECs) in vitro and enhanced osteogenic-related gene and protein expression in ADSCs, thus promoting osteogenic differentiation. After implantation into the femoral defects of rabbits, the bioactive scaffold promoted vascular network formation and the expression of osteogenesis-related proteins, thus effectively accelerating bone regeneration. Therefore, the osteogenic and angiogenic bioactive scaffold comprising a 3D printed porous titanium alloy scaffold, PRP, and ADSCs provides a promising design for orthopedic biomaterials with clinical transformation prospects and an effective strategy for bone defect treatment.